B-type natriuretic peptide concentrations in contemporary Eisenmenger syndrome patients: predictive value and response to disease targeting therapy. Issue 9 (7th March 2012) - Diller, Gerhard-Paul; Alonso-Gonzalez, Rafael; Kempny, Aleksander; Dimopoulos, Konstantinos; Inuzuka, Ryo; Giannakoulas, Georgios; Castle, Lianne; Lammers, Astrid E; Hooper, James; Uebing, Anselm; Swan, Lorna; Gatzoulis, Michael; et al.
Abstract : Objective: To assess the relationship between elevated levels of B-type natriuretic peptide (BNP) and outcome in patients with Eisenmenger syndrome. Design: Retrospective study. Setting: Tertiary centre for adult congenital heart disease. Patients: All patients with Eisenmenger syndrome (n=181, age 36.9±12.1 years, 31% with Down syndrome) in whom BNP concentrations were measured as part of routine clinical care were included. Main outcome measures: The study end point was all cause mortality. Results: During a median follow-up period of 3.3 years, 20 patients (7 with Down syndrome) died. Higher BNP concentrations were predictive of all cause mortality on univariate analysis in patients with or without Down syndrome. On multivariable Cox proportional hazard analysis, BNP predicted survival independently of renal function, Down syndrome, or 6 min walk test distance (p=0.004). Temporal increases in BNP concentration were also found to predict mortality. Treatment with disease targeting therapies was associated with a significant reduction in BNP concentrations. Conclusions: BNP concentrations predict outcome in contemporary Eisenmenger patients. Increases in BNP concentrations over time are also of prognostic significance. In addition, disease targeting therapies may help to reduce BNP concentrations in this population, while treatment-naïve patients have static or rising BNP concentrations.